Bentuk Tindak Tutur Ekspresif Tokoh Dalam Novel Surga Yang Tak Dirindukan 2 Karya Asma Nadia - Annisa Febriani; Yulia Sri Hartati; Asri Wahyuni Sari (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This study aims to describe the forms of expressive speech acts of characters in the novel Heaven Yang Not Missed 2 by Asma Nadia. This type of research is qualitative research. The method used in this research is descriptive method. The data needed in this study is in the form of utterances used by characters in the novel Heaven Yang Not Missed 2 by Asma Nadia. The source of the data in this study is the novel Heaven that is Not Missed 2 by Asma Nadia. The technique of collecting data for this research is that the first technique used in this research is the basic technique of observing free engagement or SLBC. The second is note-taking technique. Third, taking inventory of data related to expressive speech acts in the novel Heaven Yang Not Missed 2 by Asma Nadia. The data validation technique in this study is the triangulation technique. The results of this study are that there are several forms of expressive speech acts in the novel Heaven Yang Not Missed 2 by Asma Nadia, namely in the novel Heaven Yang Not Missed 2 by Asma Nadia.